Emerging trends in gender war and intimate partner violence (2019)
African feminist literary texts most often document that patterns of intimate partner violence are as a result of socio-culturally imposed structuration in the hierarchy of the sexes, due to cultural determinisms. Hence, it is in most cases assumed that only, women are victims of intimate male partner violence. There are growing concerns that men may just be as well victims of intimate female perpetrated violence. This research investigates roles of female body and sexuality in perpetrating violence against men for the purpose of subverting masculine power in two selected plays from Isaie Biton Koulibaly's anthology, Encore les femmes ... toujours les femmes! The concept of bodiliness is used to investigate the amount of power the female body is able to deploy in quest for female emancipation. The research finds that radical females in the selected short stories deploy powers resident in the body and non-normative sexuality practices to script a new trend of shift in the occurrence and performance of gender violence in intimate relationships. The subversion of hegemony and relegation of male characters is contingent upon the resoluteness of the female characters to use their bodies and sexuality as weapons to undo prescribed gender norms..